Metabolic syndrome is independently associated with improved overall survival to first-line therapy with immune checkpoint inhibitors in non-small cell lung cancer - Bou Zerdan, Maroun; Ashok Kumar, Prashanth; Barrios, Dulce M.; Glidden, Alanna; Nasr, Dayana; Niforatos, Stephanie; Ghelani, Ghanshyam; Leibovitch, Jennifer; Nasr, Sandy; KC, Binod; Ombada, Mulham; Khokhar, Farzam; et al. (Frontiers in Oncology, 2023)
Background Many co-existing medical conditions may affect the outcome in patients treated with immune checkpoint inhibitors for advanced cancer. There is currently not any information on whether metabolic syndrome (MetS) impacts the clinical outcome in patients treated with immune checkpoint inhibitors (ICIs) for advanced non-small cell line cancer (NSCLC). Methods We carried out a single-center retrospective cohort study to determine the effects of MetS on first-line ICI therapy in patients with NSCLC. Results One hundred and eighteen consecutive adult patients who received first-line therapy with ICIs and had adequate medical record information for the determination of MetS status and clinical outcomes were included in the study. Twenty-one patients had MetS and 97 did not. There was no significant difference between the two groups in age, gender, smoking history, ECOG performance status, tumor histologic types, pre-therapy use of broad-spectrum antimicrobials, PDL-1 expression, pre-treatment neutrophil:lymphocyte ratio, or proportions of patients who received ICI monotherapy or chemoimmunotherapy. With a median follow-up of 9 months (range 0.5-67), MetS patients enjoyed significantly longer overall survival (HR 0.54, 95% CI: 0.31-0.92) (p = 0.02) but not progression-free survival. The improved outcome was only observed in patients who received ICI monotherapy and not chemoimmunotherapy. MetS predicted for higher probability of survival at 6 months (p = 0.043) and 12 months (p = 0.008). Multivariate analysis indicated that, in addition to the known adverse effects of use of broad-spectrum antimicrobials and the beneficial effects of PD-L1 (Programmed cell death-ligand 1) expression, MetS was independently associated with improved overall survival but not progression-free survival. Conclusions Our results suggest that MetS is an independent predictor of treatment outcome in patients who received first-line ICI monotherapy for NSCLC.